Perceived Age and Personality Profiling after Orthognathic Surgery. Issue 1 (17th May 2022) - Pourtaheri, Navid; Peck, Connor J.; Gowda, Arvind; Parsaei, Yassmin; Allam, Omar; Patel, Visha K.; Park, Eric; Yu, Jason; Lopez, Joseph; Steinbacher, Derek M.
Abstract : Background: Recent studies suggest that orthognathic surgery can improve facial age and personality profiling. The authors expand on these findings by assessing the role of patient facial profile and sociodemographics on perceived changes following surgery. Methods: Preoperative and postoperative images of 65 patients operated on by a single surgeon were randomly assorted and rated by 30 respondents. Patient facial profiles were categorized as convex, concave, or straight. Paired and unpaired t tests were used to assess differences preoperatively and postoperatively. Multivariate regression and post hoc receiver operating characteristic curve analyses were used to quantify the influence of various patient factors. Results: Significant decreases in perceived age were seen following orthognathic surgery overall (−1.31 years; p < 0.01) and in the straight (−1.10 years; p = 0.02) and convex (−1.80 years; p ≤ 0.01) subgroups. After controlling for patient sociodemographics, there were no significant differences in age change based on facial profile. Older age at the time of surgery was independently associated with greater perceived age changes ( p = 0.04); older patients (>26.5 years, determined by receiver operating characteristic curve) experienced greater net decreases in perceived age in comparison to younger patients (−2.0 years versus −1.2 years; p < 0.01). Improvements were seen in overall attractiveness ( p < 0.01) and in each tested personality characteristic following surgery ( p < 0.01). These differences were not significantly associated with different patient sociodemographics or facial profile. Conclusions: The authors' data add to the growing base of evidence that orthognathic surgery improves patient-perceived age and personality. Significant decreases in perceived age are more likely to be gained by patients undergoing surgery at an older age. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II.